Pemetaan Pengembangan Keprofesionalan Dosen Politeknik - (Jurusan Teknik Elektro, Politeknik Negeri Semarang), Eddy Triyono (Teknis, 2016)
Lecturers are professional educators and scientists with the main task of transforming, through the Science and Technology Education, Research, and Community Service. This study aims to determine the level of service each polytechnic lecturers in professional development in the implementation of Tridharma college. The research was conducted on four Polytechnic. Samples was determined using stratified random sampling technique. Data collection instrument used was a questionnaire. The results showed (1) the level of service Polines, PIP and Politekes in the professional development of lecturers in all areas A (Education and teaching), B (Research), C (Community Service), D (Supporting) category is very adequate and sufficient more of 50%; (2). Polimarin service level in the professional development of lecturers in all areas A (Education and teaching), B (Research), C (Community Service), D (Supporting) category is very adequate and sufficient less than 50%; (3). Professional development of lecturers today is the academic development by implementing the Tri Dharma of high education.Keywords: Tridharma of high education, professional lecturers, polytechnic